Geomorphological hazards on transportation roads in Sarkapkan township (Raparin Journal of Humanities (RJH), 2023)
Sarkapkan sub-district, in terms of administration, belongs to Ranya district in Slemani province. Astronomically, it is located between the located in latitude (northern Longitude °36: ¯28:꓿27-°36: ¯15: ꓿21.) (°45: ¯51: ꓿35- east °45: ¯46: ꓿39)eastern longitudes. It is located in the northwest of Slemani Province. The study area includes a strategically important economic and military road that borders with Warte sub-district in Erbil province, as well as a number of secondary roads that connect human settlements to the urban center, and in physiography is located in a hard mountainous area. The main objective of this study is to identify the environmental characteristics of the study area and draw a specific map for each of them in order to analyze the risks faced by the roads in the study area. The study begins with an analysis of the natural environment in Sarkapkan sub-district and its impact on roads, such as (geology, topography, climate, soil, and vegetation cover). In the second part, we discussed the introduction of road networks in terms of (main, secondary, and village roads) and then the role of humans in destroying the balance of the earth and as a factor in the creation of danger on roads, this is an analysis of each of these natural features and their direct and indirect impact on traffic networks. In the third part, each of the processes (water erosion and movement of materials) is discussed and their impact on the creation of hazards on the roads is examined, and then a morphodynamics map is created to determine the level of morphodynamics risk in the study area. The results of the study show that natural characteristics and human activities play a major role in the creation of geomorphological hazards on traffic networks and their destruction.